2021
DOI: 10.47577/tssj.v15i1.2240
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Impact on Public Distress, Economy and Education of Bago Division in Myanmar

Abstract: In Myanmar, two expatriates have started infected by COVID-19 pandemic on 23 March in 2020 and COVID-19 period was divided into the two periods by the data of patients, from starting July 29, no more infected people found till August 19. Myanmar citizen think that there will be no more new COVID-19 cases, they started running their daily work, not following precaution methods. Unfortunately, the number of patients increased more and more, starting from 20th August. The period between 23rd March and 19th August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In second COVID-19 wave, volunteers cannot help many families. (Marnn et al, 2021). The study showed that COVID-19 has negatively affected the poverty and living standards of house-holds and that the adverse effect was much higher for the unemployed compared to the employed.…”
Section: Latar Belakang Pelaksanaanmentioning
confidence: 92%
“…In second COVID-19 wave, volunteers cannot help many families. (Marnn et al, 2021). The study showed that COVID-19 has negatively affected the poverty and living standards of house-holds and that the adverse effect was much higher for the unemployed compared to the employed.…”
Section: Latar Belakang Pelaksanaanmentioning
confidence: 92%
“…Small research groups and research groups based in many parts of Asia and Africa, where the issues related by plastic pollution are of growing concern (e.g. Matsuguma et al, 2017;Kapinga and Chung, 2020;Marnn et al, 2021;Akindele and Alimba, 2021), may not have the financial resources to purchase the needed tools. This situation may limit the research efforts by those who do not have access to the so-called 'standard' facilities, and ultimately be detrimental to the progress and evolution of the field of plastic pollution.…”
Section: A Plea For An Interdisciplinary Approach To Micro-and Nanopl...mentioning
confidence: 99%